Becoming Hitler : the making of a Nazi - Weber, Thomas, 1974- 1974- (Basic Books, 2017)
"An award-winning historian charts Hitler's radical transformation after World War I from a directionless loner into a powerful National Socialist leader. In Becoming Hitler, award-winning historian Thomas Weber examines Adolf Hitler's time in Munich between 1918 and 1926, the years when Hitler shed his awkward, feckless persona and transformed himself into a savvy opportunistic political operator who saw himself as Germany's messiah. The story of Hitler's transformation is one of a fateful match between man and city. After opportunistically fluctuating between the ideas of the left and the right, Hitler emerged as an astonishingly flexible leader of Munich's right-wing movement. The tragedy for Germany and the world was that Hitler found himself in Munich; had he not been in Bavaria in the wake of the war and the revolution, his transformation into a National Socialist may never have occurred. In Becoming Hitler, Weber brilliantly charts this tragic metamorphosis, dramatically expanding our knowledge of how Hitler became a lethal demagogue"...